Influence of Aerobic Exercise After Static Stretching on Flexibility and Strength in Plantar Flexor Muscles - Takeuchi, Kosuke; Nakamura, Masatoshi (Frontiers in Physiology, 2020)
Aerobic exercise could improve stretch-induced strength deficits. However, mechanisms of the improvement were unclear. The purpose of the study was to examine the effects of aerobic exercise after static stretching on flexibility and isometric strength in ankle plantar-flexor muscles. Fifteen healthy males received two interventions after static stretching of their ankle plantar-flexor muscles for 5 minutes. One was aerobic exercise for 10-minutes on a cycling ergometer, and the other was a 10-minute rest as a control. Range of motion of ankle dorsiflexion, passive torque at terminal range of motion, muscle-tendon unit stiffness, muscle tendon junction displacement, peak torque of ankle plantarflexion, and the amplitude of electromyography were measured. Immediately after the static stretching, in both interventions, range of motion, passive torque, and muscle tendon junction displacement increased significantly (p < 0.05), while muscle-tendon unit stiffness, peak torque, and the amplitude of electromyography were significantly decreased (p < 0.05). After 10-minutes on a cycling ergometer, the decreased peak torque and amplitude of electromyography indicated higher values than those before static stretching (p < 0.05), while muscle-tendon unit stiffness was no change. In conclusion, static stretching increased range of motion because of the decreased muscle-tendon unit stiffness as well as increased tolerance for stretching. Aerobic exercise could increase the muscle strength and amplitude of electromyography which decreased after static stretching.